Effect of Biochar on Soil CO2 Fluxes from Agricultural Field Experiments in Russian Far East: A Recent Study - M. A. Bovsun; S. Castaldi; O. V. Nesterova; V. A. Semal; N. A. Sakara; A. V. Brikmans; A. I. Khoklova; T. Y. Karpenko (Current Topics in Agricultural Sciences Vol. 3, 2021)
Agricultural soils are a major source of greenhouse gases. Biochar is a soil improver and, when applied to the soil, sequesters carbon. An important property of biochar is the very low rate of decomposition compared with the original biomass which allows for longer residence time in the soil compared to other forms of organic amendments. However, a different combination of soil and climatic conditions and biochar leads to different research results. The purpose of our research estimate the effects of 1 kg/m2 and 3 kg/m2 biochar application to clay soils on the CO2 flow in field experiments along two cropping seasons in the Russian Far East was investigated. Data showed that biochar significantly reduces the cumulative flow of soil CO2, compared with untreated field plots. In the season 2018, the greatest reduction in soil CO2 emissions (28.2%) with 3 kg/m2 of biochar was obtained, while in 2019 the greatest decrease in the cumulative CO2 flow at the application dose of 1 kg / m2 (57.7 %) was recorded. Correlation between a decrease in the value of the cumulative CO2 flux and an increase in the biomass grown in the studied areas of agricultural crops during the season of 2018 was found.